Citrus Leaf Sampling Procedures for Nutrient Analysis - Tripti Vashisth; Jamie D Burrow; Davie Kadyampakeni; Rhuanito Ferrarezi (EDIS)
To maintain balanced nutrients for optimal tree growth, citrus growers need to assess trees’ nutritional requirements. These assessments help prevent any nutrient deficiency or toxicity from compromising tree health and yield or reducing revenue. This new illustrated two-page instructional sheet gives a basic procedure for the citrus leaf sampling process, as well as additional suggestions for HLB-affected trees. Written by Tripti Vashisth, Jamie D. Burrow, Davie Kadyampakeni, and Rhuanito S. Ferrarezi, and published by the UF/IFAS Horticultural Sciences Department. https://edis.ifas.ufl.edu/hs1355